Incorporação de resíduos de vidro do tipo “garrafas long neck” em blocos de concreto - Carvalho, Mariana Novaes (2021)
Changes in the population consumption habits have contributed to increase the glass waste (RV), such as glass beer bottles, which have aggravated the problem of overcrowding landfills and dumps. Due to the high cost for the reuse of these bottles in the manufacturing process, the incorporation of this waste in the most different materials has been studied in order to minimize the impact caused by this waste to the environment. Thus, the substitution of natural aggregates in concrete mixtures by RV has been technically viable and an ecofriendly alternative. Nevertheless, in order to offer an alternative destination for these glass beer bottles, this research has incorporated at dry-mixed concrete for blocks, proportions of 10, 20 and 30% of RV in replacement of the sand and evaluated the mechanical properties as compressive strength and water absorption in 7 and 28 days. Through the results, can be concluded that the incorporation of RV improved these characteristics, with a compressive gain until 30% of RV. Furthermore, all the concrete blocks with glass waste addition, showed water absorption rates lower than the control mix.